Preparing TVET Instructors in Nepal: Challenges and Way Forward - Kunwar, Pratima; Odjo, Zinsou Cosme; Baral, Durga Prasad (Journal of Technical and Vocational Education and Training, 2025)
Instructors of the Technical and Vocational Education and Training (TVET) play a crucial role in developing skilled human resource for the country by transferring market relevant skills. However, some instructors face challenges to give best in their roles. Therefore, removing the barriers before instructors and keeping them motivated with a conducive environment is imperative. The purpose of this research article is to investigate the challenges and considerations in preparing TVET instructors in Nepal. This study was conducted using a qualitative research methodology. It focused on four provinces of Nepal with Human Development Index (HDI) values. Both primary and secondary sources of information were collected. A total of ten participants, including TVET instructors and principals and managers from both public and private institutions, were purposefully selected.Qualitative information was collected by using online Google form, and thematic analysis was used to assess the information.The findings of this study uncovered several significant challenges in preparation of TVET instructors in Nepal. The challenges include lack of industry relevant curriculum to address the need of real world scenario, absence of instructors' contribution in curriculum designing, inadequate professional development opportunities to the instructors, particularly beyond the constituent schools, insufficiency of practical knowledge of emerging technologies, lack of proper training need assessment of instructors, dearth of industry experience, absence of systematic performance management system and low motivation to instructors.The findings demonstrate the strong need to address the challenges and increase motivation to the instructors.